Stabilizing High-Voltage Cathodes via Ball-Mill Coating with Flame-Made Nanopowder Electrolytes - Yu, Mengjie; Brandt, Taylor G.; Temeche, Eleni; Laine, Richard M. (ACS applied materials & interfaces, 2022)
LiMn1.5Ni0.5O4 (LMNO) spinel has recently been the subject of intense research as a cathode material because it is cheap, cobalt-free, and has a high discharge voltage (4.7 V). However, the decomposition of conventional liquid electrolytes on the cathode surface at this high oxidation state and the dissolution of Mn2+ have hindered its practical utility. We report here that simply ball-mill coating LMNO using flame-made nanopowder (NPs, 5–20 wt %, e.g., LiAlO2, LATSP, LLZO) electrolytes generates coated composites that mitigate these well-recognized issues. As-synthesized composite cathodes maintain a single P4332 cubic spinel phase. Transmission electron microscopy (TEM) and X-ray photoelectron spectra (XPS) show island-type NP coatings on LMNO surfaces. Different NPs show various effects on LMNO composite cathode performance compared to pristine LMNO (120 mAh g–1, 93% capacity retention after 50 cycles at C/3, ∼67 mAh g–1 at 8C, and ∼540 Wh kg–1 energy density). For example, the LMNO + 20 wt % LiAlO2 composite cathodes exhibit Li+ diffusivities improved by two orders of magnitude over pristine LMNO and discharge capacities up to ∼136 mAh g–1 after 100 cycles at C/3 (98% retention), while 10 wt % LiAlO2 shows ∼110 mAh g–1 at 10C and an average discharge energy density of ∼640 Wh kg–1. Detailed postmortem analyses on cycled composite electrodes demonstrate that NP coatings form protective layers. In addition, preliminary studies suggest potential utility in all-solid-state batteries (ASSBs).